Does the Promotion variable moderate the Customer Satisfaction Variable Adam's Fashion? - Mahri, A. Jajang W.; Juliana, Juliana; Saepudin, Saepudin; Firmansyah, Firmansyah (PINISI Discretion Review, 2022)
To determine the effect of product quality, price, Islamic marketing, promotions and promotions as moderating variables on consumer satisfaction. The method used in this study is a quantitative method with a causality descriptive research design. The analysis tool used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS application. The subjects of this study were Adam's consumers with a sample of 212. The results of the study show that product quality, price, Islamic marketing have a positive effect on consumer satisfaction, while promotion does not moderate the product quality, price and Islamic marketing variables on customer satisfaction. Adam needs to make efforts to maximize consumer satisfaction. Some of the efforts that Adams can make to maximize consumer satisfaction are by increasing product quality at prices adjusted to quality and supported by Islamic marketing in boosting sales and convincing consumers to buy products. This study is the first to testthe influence of Islamic marketing coupled with promotion as a moderating variable on consumer satisfaction.